2021
DOI: 10.3233/jhd-200414
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair in Huntington’s Disease and Spinocerebellar Ataxias: Somatic Instability and Alternative Hypotheses

Abstract: The use of genome wide association studies (GWAS) in Huntington’s disease (HD) research, driven by unbiased human data analysis, has transformed the focus of new targets that could affect age at onset. While there is a significant depth of information on DNA damage repair, with many drugs and drug targets, most of this development has taken place in the context of cancer therapy. DNA damage repair in neurons does not rely on DNA replication correction mechanisms. However, there is a strong connection between D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 99 publications
3
14
0
Order By: Relevance
“…Our data are in line with previous EM studies from human HD patients 95 and HD mice models 19,96 showing nuclear ultrastructural changes, including altered nuclear membrane shape, nuclear invagination and increased nuclear pore density in neurons bearing Httex1 inclusions. Consistent with these observations, the nuclei containing Httex1 72Q inclusions showed enhanced nuclear condensation over time (Figure 5E), indicating increased neuronal toxicity, consistent with previous reports in HD patients 97 and HD mice model 96 . Interestingly, despite the presence of the large inclusions as early as D3 in the neurons overexpressing Δ Nt17 Httex1 72Q, we did not observe an earlier onset of cell death or a higher level of toxicity over time in these neurons compared to those overexpressing Httex1 72Q (Figure 5E).…”
Section: Expression Of Httex1 72q In Primary Cortical Neurons Leads To the Formation Of Dense And Filamentous Nuclear Inclusionssupporting
confidence: 92%
“…Our data are in line with previous EM studies from human HD patients 95 and HD mice models 19,96 showing nuclear ultrastructural changes, including altered nuclear membrane shape, nuclear invagination and increased nuclear pore density in neurons bearing Httex1 inclusions. Consistent with these observations, the nuclei containing Httex1 72Q inclusions showed enhanced nuclear condensation over time (Figure 5E), indicating increased neuronal toxicity, consistent with previous reports in HD patients 97 and HD mice model 96 . Interestingly, despite the presence of the large inclusions as early as D3 in the neurons overexpressing Δ Nt17 Httex1 72Q, we did not observe an earlier onset of cell death or a higher level of toxicity over time in these neurons compared to those overexpressing Httex1 72Q (Figure 5E).…”
Section: Expression Of Httex1 72q In Primary Cortical Neurons Leads To the Formation Of Dense And Filamentous Nuclear Inclusionssupporting
confidence: 92%
“…The requirement of MMR complexes-including MutS␣ (MSH2-MSH3), MutS␤ (MSH2-MSH6), MutL␣ (MLH1-PMS2) and MutL␥ (MLH1-MLH3)-in CAG/CTG, CGG/CCG, and GAA/TTC repeat instability has been extensively studied [185,210,213,[222][223][224][225][226][227][228][229]. MustS␤ (MSH2-MSH3), through its ability to bind slip-DNA structures, may facilitate their formation [210].…”
Section: Role Of Fan1 In Repair-associated Repeat Instabilitymentioning
confidence: 99%
“…Swami et al [14] investigated somatic expansion in post-mortem DNA samples from HD patients, and showed that patients with particularly early-onset have a higher proportion of large expansions in the cortex. Most recently, genetic association studies in HD patient cohorts have revealed the association between DNA repair gene variants and age at motor signs of HD and HD progression [15][16][17][18][19]. These data suggest that somatic CAG repeat expansions contribute toward HD pathology.…”
Section: Introductionmentioning
confidence: 97%
“…More detailed quantitative analyses of the dynamics of somatic mosaicism should help to answer some of these questions, and further disentangling of the mechanisms by which they are generated should allow for the identification of additional therapeutic targets. Although several components of the DNA mismatch repair pathway have been shown to be critical for somatic expansion [12,[20][21][22][23], the precise molecular processes that generate expansions and determine their tissue specificity is unknown [18,19,24,25]. In this context, precise and accurate quantification of HTT CAG somatic mosaicism in patient samples and model systems is warranted, since it may provide a suitable phenotype for genetic association studies aimed at identifying genetic variants that act as modifiers of repeat instability [7,15].…”
Section: Introductionmentioning
confidence: 99%